À margem da história, no centro das narrativas: análise das práticas leitoras de adolescentes internos em centros de recuperação para menores infratores, no Estado do Rio de Janeiro. - Ribeiro, Maria Aparecida S. (Cadernos de Linguagem e Sociedade, 2010)
Story is a basic principle of mind. Most of our experience, our knowledge, and our thinking is organized as stories. The mental scope of story is magnified by projection ”“ one story helps us make sense of another. (M. Turner) In this text, we analyze the power of this projection, and how it works. Our readers imagine realities and construct meanings in their practices of reading by the same basic mechanisms of the literary. “How and why we project one story onto another” is our question.